The Relationship Between Middle Income Trap and Structural Transformation The Case of Selected Countries - Soyyiğit, Semanur (Central European Journal of Economic Modelling and Econometrics, 2019)
Many studies on middle income trap draw attention to the product trap that can be expressed as the fact that countries are stuck in the production and export of unsophisticated products. In this sense, it is stated that the role of a country in the production and export of sophisticated goods is one of the determinant factors to increase the level of income. In the literature, the concept of economic complexity, which is expressed as gaining competitiveness of complex products in terms of production and export, is noteworthy in recent years. In this framework, relationship between the per capita GDP and the economic complexity is examined with regression analysis in this study for selected countries with high-level of income. In the analysis, in which random coefficient panel regression model is applied, a significant relationship was found between the two variables for Austria, Finland, Hong Kong, Japan, Norway, Singapore and Sweden.